HUBUNGAN PENGHIMPUNAN DANAMASYARAKAT DENGAN PENYALURAN KREDIT BANK RAKYAT INDONESIA (BRI)CABANG SANGGAU - Lesmaya B01107084, Vidya Sutra (Jurnal Pembangunan dan Pemerataan, 2014)
This tesearch gets title â€œThe Influence of Third Party Fund Realization (Lents Fund Society) to Credit Channelizing ofSanggau's BranchIndonesian People Bank (BRI),â€ by Vidya Sutra Lesmaya, are one case study research on PT BRI Sanggau West Kalimantan's Regency Branch. To the effect research is know and analizingof Â influence of lents fund societyÂ  to working capital credit realization, investment credit realization, and consumptive credit realization that channelled by PT. BRI Sanggau's Branch,observational period 2008 to 2012. This research by descriptive observational andÂ  quantitative analizing, The Â analisis's tool that utilized with simple regression. Observationalâ€™s variable isÂ  realization lents of fund society Â (third party fund) as free variable (independent variabel), and there are three variabel (dependent variabel) of this research,Â  they arerealizations of working capitals credit, investment credit, and consumptive credit realization. The data utilized by stem of BRI'S Bank reporting of Sanggau Branc bases quartal (4monthly) reporting of year 2008 until 2012. Itâ€™s result observationaling to point out that DPK'S relationship with a realization of Working Capital Credit, Investment credit and also Consumptive Credit is positive, different correlation coefficient point each other. The correlation coefficient among DPK on credit Working Capital very poor (0,149), its mean if DPK high, therefore working capital credit will also increase as big as 0,149 times. While enough Investment Credit correlation coefficient strong as big as 0,619, its mean if DPK'S amount increases one time, therefore investment credit increases as big as 0,619 times. Meanwhile correlation coefficient among DPK on credit Consumption also frail (0,355), its mean if DPK increases one time, therefore consumes credit realization will increase as big as 0,355 times. DPK's zoom lents fund society not so far-reaching to increase of credit realization, it because of that main more credit realization regarded by BRI'S bank and a home office policy, also sides bank just get profit's orientation and security judgment/credit return fluency it, without paying atention of origin lents fund that will be realization. Â  Key word:Â  Â Â  Working capital credit, investment credit, consumptive credit, lents fund society,third party fund.